Karakteristik Terasering Lahan Sawah dan Pengelolaannya di Subak Jatiluwih, Kecamatan Penebel, Kabupaten Tabanan - DEVI LEORENSIA BOKINGS; I NYOMAN SUNARTA; I WAYAN NARKA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
ABSTRACT The Characteristic of Wetland Terracing in the Hillside Area and Its Management at Subak Jatiluwih, Sub-district of Penebel, Regency of Tabanan Subak Jatiluwih has a characteristic of rice field terracing which sufficiently taken into account as a terrace model and rice field management in the hillside area. In order to get the terrace model along with rice field management in the hillside area required a research regarding the subak land terracing characteristic in the hillside area along with its management. The research carried out by the method of survey and soil samples taken were analyzed in the laboratory the soil, and data management of terrace land were obtained through interviews to farmers landowners of sample. The research aims to find out the terrace along with the form of its land management, which is in the form of cropping pattern and irrigation system existed at Subak Jatiluwih, Sub-district of Penebel, Regency of Tabanan. The result of research shows that the steeper the class of hillside’s slope is, the narrower its terrace’s width, the higher its terrace’s height, the wider its rice field’s width, the higher its rice field’s height, the lower its inner rice field’s height, and the greater its rice field’s slope angle to its vertical plane. The cropping pattern being used at Subak Jatiluwih is cropping pattern of paddy-paddy-paddy and cropping pattern of paddy-paddy. The irrigation system applied is continuous simultaneously flowing system or continuous flow which does not need too many personnel to operate it.   Keyword : Slope,  Bench Terrace, Cropping Pattern, Irrigation System